Teacher’s personality and self-fulfilling prophecy - Raftoulis, Georgios; Koniari, Dimitra (Papanda Publisher, 2025)
The present study aims to examine the interaction of teacher’s personality in accordance to self-fulfilling prophecy. Especially, the purpose of this survey is to investigate the role of teachers’ self-fulfilling in the crucial of education and if and in which extend it is influenced by the personality of every teacher. No one can dispute that self-fulfilling prophecy is so important that it can determine the interactions between teachers and students. This specific investigation resulted from the literature review carried out and from conducting a quantitative survey on a sample of 291 teachers the period January- May 2024 in Greece. From the analysis that followed, it emerged that factors such as gender, age, political ideology, receptivity to experience, the degree of intragroup valence do not contribute to the strengthening of self-fulfilling prophecy.. On the contrary, the degree of social hierarchy and authoritarianism are decisive factors that affect teachers’ self-fulfilling